(untitled) (Fisioterapia e Pesquisa, 2022)
To analyze why we should care for term infants admitted to a neonatal intensive care unit. Documented, descriptive, retrospective study of 262 term newborns (NB). Variables used: NB characteristics; main diagnosis, length of stay and follow-up by the multiprofessional team; post-discharge referral. There was a predominance of male gender (52%), Apgar score nine in the 5th minute, race/color of the newborn and mother was white (61.1% and 48.9% respectively). The main diagnosis was respiratory dysfunction (28.8%). Length of stay was eight days. There was a significant difference between length of stay (p=0.013), in which cardiorespiratory and other diseases stayed less time compared to malformation or maternal diseases. The social service was the most sought (81.2%) and physiotherapy the least sought (18%). NB with higher weight were hospitalized for less time. Those followed by physiotherapy had longer stay (p<0.001). Main outcome was hospital discharge (68.7%) and referrals to the Basic Health Unit (57%). The findings of this study pointed to less severe babies, low number of specific studies for the term population, other diagnoses that refer us to non-intensive care.